Exceptional ability of blind humans to hear sound motion: Implications for the emergence of auditory space - Lewald, Jörg (Neuropsychologia, 2013)
Blind people may compensate for their visual loss by the increased use of auditory spatial information, thus showing normal or even supra-normal ability to localize sources of sound. However, the problem of how blind persons develop and maintain an internal concept of the topography of the auditory space in the absence of calibration by visual information is still unsolved. The present study demonstrated a substantial superiority of blind subjects in perception of auditory motion: The minimum audible movement angle of blind subjects (mean 3°) was about half the value found in matched sighted controls, whereas no such advantage was demonstrable for localization of stationary sound. There were no significant differences between early or congenitally blind subjects and late blind subjects, suggesting that long-term visual deprivation per se, independently of the point in time of its onset, was relevant for the superiority in auditory motion perception. The results were compatible with the hypothesis that in the absence of visual input the calibration of the auditory space is performed by audiomotor feedback, that is, by the evaluation of systematic changes of auditory spatial cues resulting from head and body movements. It is reasonable to assume that with blindness the neuronal circuits specifically concerned with the analysis of auditory motion are more intensely trained than in sighted people. It seems possible that the higher demand of motion analysis associated with blindness is related to processes of reorganization in the brain, as have been previously reported to occur also in areas known to be involved in auditory and/or visual motion analysis in sighted persons. ► Blind subjects showed a substantial superiority in perception of auditory motion. ► Their minimum audible movement angle was only half the value of sighted controls. ► This supports the model of calibration of auditory space by audiomotor feedback.